2006
DOI: 10.2353/ajpath.2006.051109
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transducers and Activators of Transcription-3 Up-Regulates Tissue Inhibitor of Metalloproteinase-1 Expression and Decreases Invasiveness of Breast Cancer

Abstract: Signal transducers and activators of transcription (STAT)-3 is an oncogenic protein that is constitutively activated in many human cancers, including 30 to 60% of primary breast cancer. The biological significance of STAT3 activation in breast cancer is not fully understood. We have previously shown that STAT3 up-regulates tissue inhibitors of metalloproteinase (TIMP)-1, a cytokine known to block metalloproteinases and decrease invasiveness in certain cancer cell types. We hypothesize that STAT3 activation may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 50 publications
0
32
0
1
Order By: Relevance
“…Interestingly, STAT3 is constitutively activated in ∼50%-60% of primary breast tumors and its downregulation decreases the tumorigenecity of breast cancer cells (Dien et al 2006). Moreover, recent loss-of-function studies have demonstrated OCT4 as an important mediator of some cancer cell phenotypes (Chang et al 2008) and NANOG as a biologically functional regulatory molecule in tumor development (Jeter et al 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, STAT3 is constitutively activated in ∼50%-60% of primary breast tumors and its downregulation decreases the tumorigenecity of breast cancer cells (Dien et al 2006). Moreover, recent loss-of-function studies have demonstrated OCT4 as an important mediator of some cancer cell phenotypes (Chang et al 2008) and NANOG as a biologically functional regulatory molecule in tumor development (Jeter et al 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, mRNA for IRF-8 and IRF-3 were increased in the ascending aorta of MPS I mice, and these proteins may function in a similar fashion on the cathepsin S promoter as IRF-1 [27]. In addition, TIMP-1 is regulated by STAT-3 [38], and its mRNA was 4-fold normal (Fig. 2).…”
Section: Role Of Stat Proteins In Upregulation Of Mmp-12 and Cathepsin Smentioning
confidence: 95%
“…Recent results from gene profiling analysis indicate that the expression signature of primary HCC is very similar to that of its corresponding metastases, suggesting that transcriptional changes which control metastatic progression are initiated in the primary tumors [251]. STAT3 however, is also known to upregulate tissue inhibitors of metalloproteinase TIMP-1, a cytokine known to block metalloproteinases and decrease invasiveness in certain cancer cell types [252]. STAT3 also controls the expression of the MUC1 gene, which can mediate tumor invasion [253].…”
Section: Role Of Stat3 In Cellular Invasionmentioning
confidence: 99%